2021
DOI: 10.1177/15266028211016423
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Advanta V12 Covered Stents After Fenestrated Endovascular Aneurysm Repair

Abstract: Purpose: Fenestrated endovascular aneurysm repair (FEVAR) is a well-established endovascular treatment option for pararenal abdominal aortic aneurysms in which balloon-expandable covered stents (BECS) are used to bridge the fenestration to the target vessels. This study presents midterm clinical outcomes and patency rates of the Advanta V12 BECS used as a bridging stent. Methods: All patients treated with FEVAR with at least 1 Advanta V12 BECS were included from 2 large-volume vascular centers between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…A substantial proportion of post-FEVAR reinterventions have to be performed to treat BECS-associated complications. 1 , 2 Physicians often need, however, to perform selective angiography of all BECSs during the reintervention procedure to identify whether the BECS is causing the problem. Flare geometry analysis may be helpful to detect BECS-associated complications to plan a reintervention and limiting radiation exposure and contrast use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial proportion of post-FEVAR reinterventions have to be performed to treat BECS-associated complications. 1 , 2 Physicians often need, however, to perform selective angiography of all BECSs during the reintervention procedure to identify whether the BECS is causing the problem. Flare geometry analysis may be helpful to detect BECS-associated complications to plan a reintervention and limiting radiation exposure and contrast use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that 33% to 52% of all reinterventions after FEVAR are performed for complications associated with BECS, such as type 3c endoleak, BECS stenosis, BECS occlusion, or stent fracture. 1 , 2 Detecting the origin of an endoleak after FEVAR can be difficult to appreciate on standard computed tomographic angiography (CTA) scans. Often additional selective angiography is necessary to detect which of the BECS is the source of a BECS-related endoleak of other complications.…”
Section: Introductionmentioning
confidence: 99%
“…The dataset of this retrospective study comprised patients treated with FEVAR between January 2012 and April 2021 in the University Medical Center Groningen, the Netherlands, and between January 2012 and December 2015 in the General Hospital, Nuremberg, Germany. The FEVAR-patients treated between January 2012 and December 2015 have been described in a previous study [ 11 ]. All patients underwent primary FEVAR to treat a JAAA or to treat a previous failed EVAR and at least one fenestration had to be stented with an Advanta V12 BECS.…”
Section: Methodsmentioning
confidence: 99%
“…A substantial 115 proportion of post-FEVAR reinterventions have to be performed to treat BECSassociated complications. [13,135] Physicians often need, however, to perform selective angiography of all BECSs during the reintervention procedure to identify whether the BECS is causing the problem. FGA may be helpful to detect BECSassociated complications in order to plan a reintervention and limiting radiation exposure and contrast use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that 33% to 52% of all reinterventions after FEVAR are performed for complications associated with BECS, such as type 3c endoleak, BECS stenosis, BECS occlusion or stent fracture. [13,135] Detecting the origin of an endoleak after FEVAR can be difficult to appreciate on standard CTA scans. Often additional selective angiography is necessary to detect which of the BECS is the source of a BECS-related-endoleak of other complication.…”
Section: Introductionmentioning
confidence: 99%